Developmental Regulation and Awareness of Age-Related Change: A (Mostly) Unexplored Connection. (20th July 2016) - Dutt, Anne J; Gabrian, Martina; Wahl, Hans-Werner
Abstract: Objectives: Linkages between developmental regulation and awareness of aging—although suggested by theoretical considerations—have not found much empirical consideration. To address this gap, we examined associations between two established modes of developmental regulation, that is, assimilation and accommodation, and awareness of age-related change (AARC) in midlife and old age, while considering the role of chronological age as a moderator. Method: Data are based on a cross-sectional sample of 356 adults (aged 42–100 years). A newly developed measure of AARC was used to assess perceived gain- and loss-related aging experiences. Results: AARC was associated with assimilation and accommodation over and above a range of control variables. Individuals who perceived many loss-related aging experiences were less likely to use assimilation and accommodation. Individuals perceiving many gain-related aging experiences were more likely to make use of these strategies. The effects remained stable when controlling for subjective age and self-efficacy, except for the association between gain-related aging experiences and assimilation. No moderation effect of calendar age was found. Discussion: Results suggest that multidimensional subjective aging constructs may enrich our understanding of how developmental regulation modalities are used by aging individuals.